Imaging Tests in the Diagnosis of Pulmonary Embolism - Mos, Inge C.M.; Klok, Frederikus A.; Kroft, Lucia J.M.; de Roos, Albert; Huisman, Menno V. (Seminars in Respiratory and Critical Care Medicine, 2012)
Imaging modalities play an essential role in diagnosing pulmonary embolism (PE). Clinical outcome studies demonstrated that PE can be safely ruled out in patients with unlikely clinical probability in combination with a normal D-dimer test result; in all other patients additional imaging is needed. The aim is to accurately confirm or rule out the diagnosis of PE, after which, if indicated, anticoagulant treatment can be initiated. Various diagnostic tests are available, and this article reviews the different imaging techniques in patients with suspected PE. Computed tomographic pulmonary angiography (CTPA) is the imaging test of choice because of its high sensitivity and specificity. Compression ultrasonography and ventilation perfusion scintigraphy are reserved for patients with concomitant suspicion of deep vein thrombosis or contraindication for CTPA. Furthermore the diagnostic process in patients with clinically suspected recurrent PE, PE during pregnancy, and PE in the elderly and in patients with malignancy are discussed.
Keywords: pulmonary embolism; venous thromboembolism; imaging; CT angiogram; ventilation/perfusion scan; compression ultrasonography; D-dimer